Efektivitas instalasi pengelolaan air limbah komunal program Usri 2014 di Kecamatan Depok Sleman - Noor Rosyidah Amini; Sarto Sarto (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: To find out the relationship of capacity design toward effectiveness of Waste Water Treatment Plant (WWTP) Methods: This study was an observational study, using a cross-sectional design. Method of sampling of waster water is done by grab sampling method. The data analysis used a descriptive analysis. Results: The results showed that the highest level of effectivity of BOD and TSS are 91,09% and 97,50%. The level of MPN coliform and MPN E.coli are >1600x102 MPN/100ml, it means exceeded the quality standard of waste water. Suitability of capacity design with operational of WWTP including discharge, number of users, level of BOD and TSS, level of MPN Coliform and MPN E.coli are more appropriate, the effectiveness in processing both of BOD and TSS also increased. Conclusion: there is a trend between the design capacity of WWTP to the effetiveness of BOD and TSS levels. The more appropriate the design with operational, the higher the level effectiveness of BOD and TSS levels.